Does Content Count? Constitutionality and Enforceability of Entrenchment Provisions in Aotearoa New Zealand - Oakley, Florence (Victoria University of Wellington Law Review, 2025)
Recent commentary on the enforceability of entrenchment has signalled a marked shift from Diceyan orthodoxy. This emergent view suggests that Parliament is legally obliged to comply with enhanced procedural requirements, despite their ostensible contravention of parliamentary sovereignty. The precariousness of this understanding was highlighted by the Green Party's proposal in November 2022 to entrench an anti-privatisation provision in the Water Services Entities Bill at a 60 per cent threshold. The provision was passed under urgency and, following critical backlash, swiftly repealed. This article argues that two constitutional conventions have developed in the wake of this commotion. These conventions require that entrenchment clauses uphold democratic fundamentals and set a threshold of a parliamentary supermajority of 75 per cent. Further, this article contends that the enforceability of entrenchment provisions is predicated on their content: they must uphold the functioning of representative democracy. This is due to a change in the rule of recognition driven by more nuanced understandings of parliamentary sovereignty and its place in the constitution.